Glycyrrhizae Radix Methanol Extract Attenuates Methamphetamine-Induced Locomotor Sensitization and Conditioned Place Preference. (15th October 2014) - Zhao, ZhengLin; Kim, Young Woo; Yang, YuPeng; Zhang, Jie; Jung, Ji Yun; Chang, Suchan; Cho, Il Je; Zhou, FuBo; Zhao, JunChang; Lee, Bong Hyeo; Yang, Chae Ha; Kim, Sang Chan; et al.
Abstract : Glycyrrhizae Radix modulates the neurochemical and locomotor alterations induced by acute psychostimulants in rodents via GABAb receptors. This study investigated the influence of methanol extract from Glycyrrhizae Radix (MEGR) on repeated methamphetamine- (METH-) induced locomotor sensitization and conditioned place preference (CPP). A cohort of rats was treated with METH (1 mg/kg/day) for 6 consecutive days, subjected to 6 days of withdrawal, and then challenged with the same dose of METH to induce locomotor sensitization; during the withdrawal period, the rats were administered MEGR (60 or 180 mg/kg/day). A separate cohort of rats was treated with either METH or saline every other day for 6 days in METH-paired or saline-paired chambers, respectively, to induce CPP. These rats were also administered MEGR (180 mg/kg) prior to every METH or CPP expression test. Pretreatment with MEGR (60 and 180 mg/kg/day) attenuated the expression of METH-induced locomotor sensitization dose-dependently, and 180 mg/kg MEGR significantly inhibited the development and expression of METH-induced CPP. Furthermore, administration of a selective GABAb receptor antagonist (SCH50911) prior to MEGR treatment effectively blocked the inhibitory effects of MEGR on locomotor sensitization, but not CPP. These results suggest that Glycyrrhizae Radix blocked repeated METH-induced behavioral changes via GABAb receptors.